The Self, Civic Virtue, and Public Life Interdisciplinary Perspectives - Snow, Nancy E. (Routledge Studies in Ethics and Moral Theory, 2024)
This volume showcases new and interesting ways in which the possession of civic virtues can contribute to people's abilities to engage in public life in meaningful ways. What is the role of civic virtues in public life? How does possessing civic virtues affect persons and their capacities for participation in the public order? The chapters in this volume combine philosophical and empirically informed work to show how civic virtues can be informed by larger virtue ethical perspectives. The first two chapters discuss virtues of individuals that have not received significant empirical attention-authenticity and wisdom and psychological resilience. The next two chapters address education and the ways in which civic virtues can help us to better serve schoolchildren who are socially and economically disadvantaged, as well as to broaden students' horizons with respect to character and sustainability education. The final four chapters explore the roles for virtues within various political and public realms. They offer perspectives on how virtues affect contentious politics in democratic societies, and study virtues in contexts in which democracy has been stifled or torn apart by war. Together, the chapters highlight the ever-widening impact of the virtues on our lives and in society. The Self, Civic Virtue, and Public Life will be of interest to scholars and graduate students working in ethics, political philosophy, psychology, and philosophy of education. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 International license.